INOVASI PEMBUATAN PRODUK NUGGET ANALOG BERBAHAN DASAR TEMPE DAN JANTUNG PISANG KEPOK SEBAGAI ALTERNATIF SUMBER PROTEIN DAN SERAT - Agustin, Wida Ayunindya; Saati, Elfi Anis; Siskawardani, Devi Dwi (Universitas Muhammadiyah Malang, 2023)
Abstract. Vegan is a lifestyle of someone who does not consume products derived from animal raw materials. Nuggets are food products made from various types of meat, including fish and chicken meat. The disadvantages of chicken nuggets are that they contain high fat and low fiber. Tempeh and banana blossoms were chosen because they have the advantages of high protein content and high fiber. The research design used in this study was a randomized group design consisting of 6 treatments and 3 replications. The added treatment was the proportion of tempeh and kapok banana blossom with the proportions (100%:0%, 90%:10%. 80%:20%, 70%:30%, 60%:40%, and 50%:50% ). The best treatment proportion was P1 with a ratio of 80% tempe: 10% banana flower with 49.11% water content, 0.89% ash content, 19.33% fat content, 4.29% fiber content, 22.50% carbohydrate content , and protein content 9.05%, organoleptic color 5.72 (bright), aroma 4.64% (fragrant), 4.04 (tasty), texture 4.20 (a bit soft) and preference (like). Keywords: nuggets, kepok banana heart, tempeh, protein, fiber